The socio-cultural effect of the Olympic Games on society - Slaiby, Naaman (Πανεπιστήμιο Πελοποννήσου, 2023)
Hosting the Olympic Games is a complex endeavor that countries overtake that might have numerous effects, including lasting effects on the social and cultural level. The aim of this study is to examine the socio-cultural impact of hosting the Olympic Games, including its potential benefits and drawbacks, both during and after the event. This is achieved through investigating the impact of hosting the Games on the community and culture of the host country, exploring how it promotes diversity and inclusion, and assessing its long-term impact on the host city's economy, society, and culture, as well as its international image and reputation. In order to assess the impact of hosting the socio-cultural impact of hosting the Olympic Games, this study follows a qualitative research approach that collects data through an interview from attendees of the 58th annual young participant session at the International Olympic Academy in Olympia, Greece. Six individuals filled the questionnaire, and the data collected from the interviewed was thematically analyzed, providing a better understanding about the impacts of hosting the Olympic Games. Regarding the findings of the study, three main themes were recurrent throughout the interviews, being the “positive impact on community and culture”, the “promotion of diversity and inclusion”, and the “long-term impact on the host city”. Finally, there are various recommendations that could be presented following the research, including the assessment of the pros and cons of hosting the Olympic Games beforehand, as well as including the community in the decision to host the games.
Keywords: Πόλεις υποδοχής - Κοινωνικές απόψεις; Ολυμπιακά αθλήματα - Κοινωνικές απόψεις; Φιλοξενία αθλητικής εκδήλωσης - Πολιτιστικές απόψεις; Πολιτιστικός πλουραλισμός; Host cities - Social aspects; Olympic games - Social aspects; Hosting of sporting event - Cultural aspects; Cultural pluralism; Olympic Games; Social impact; Long-term impact; Cultural impact; Diversity and inclusion